Efektivitas Pembelajaran Pendidikan Agama Kristen Bagi Murid Kelas Tujuh dan Delapan di Sekolah Menengah Pertama Negeri Satu Maesaan Kecamatan Minahasa Selatan - Yunita Nefolia Lokas; Marthin Dani Martoyo; Marde Christian Stenly Mawikere (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2021)
This iarticle iis ian iempirical iresearch ion ithe ieffectiveness iof iteaching iChristian iReligious iEducation i(PAK) ifor i7th iand i8th igrade istudents iat iSMP iNegeri i1 iMaesaan. iThis iresearch iis ia iqualitative iresearch iusing ia idescriptive iapproach ithat iwas icarried iout iat iSMP iNegeri i1 iMaesaan ilocated iin iTambelang iVillage, iMaesaan iDistrict, iSouth iMinahasa iRegency, iNorth iSulawesi iin ithe iperiod i2020-2021. The idata iin ithe istudy iwere icollected iand iprocessed ithrough iobservation, iinterviews iand idocumentation istudies. iFrom ithe iresults iof ithe iresearch idata, ithere iare iindications ithat ithere iare ilimitations ior ilack iof ieffectiveness iof ilearning iChristian iReligious iEducation iin i7th iand i8th igrade istudents iat iSMP iNegeri i1 iMaesaan. iFurthermore, iit iraises ivarious iproblems iin iChristian iReligious iEducation iLearning. iFurthermore, iit ishows ithe iimportance iof iefforts ito iovercome iproblems iin iincreasing ithe ieffectiveness iof ilearning iChristian iReligious iEducation iin i7th iand i8th igrade istudents iat iSMP iNegeri i1 iMaesaan. From ithe ifindings iand idiscussion, iit iis ihoped ithat ithe ischool, iin ithis icase ithe ischool ileadership, iwill ipay imore iattention ito iteachers iwho ihave iqualifications, icompetencies iand iprofessionals iwho imust iteach iin iChristian iReligious iEducation ilearning. iIn iother iwords, iit iis ihoped ithat ithe ischool ican iprepare ia iqualified iteacher ias ia iChristian iReligious iEducation iteacher.